Timing of sepsis is an important risk factor for white matter abnormality in extremely premature infants with sepsis - Ju Sun Heo; Ee-Kyung Kim; Young Hun Choi; Seung Han Shin; Jin A Sohn; Jung-Eun Cheon; Han-Suk Kim (Pediatrics and Neonatology)
Background: Systemic infection is a major upstream mechanism for white matter abnormality (WMA). Our aim was to evaluate the risk factors for moderate-to-severe WMA in extremely premature infants (gestational age < 28 weeks) with neonatal sepsis. Methods: Extremely premature infants with culture-proven sepsis between 2006 and 2015 in a tertiary neonatal intensive care unit were classified as having none-to-mild or moderate-to-severe WMA based on WM scores of brain magnetic resonance imaging at the term-equivalent age. Various risk factors for WMA were analyzed. Results: Sixty-three infants (87.5%) had none-to-mild WMA, and nine infants (12.5%) had moderate-to-severe WMA. Multivariate logistic regression analysis revealed that postmenstrual age (PMA) at sepsis diagnosis (OR: 0.640, 95% CI: 0.435–0.941, p = 0.023) and PMA at sepsis diagnosis <28 weeks (OR: 9.232, 95% CI: 1.020–83.590, p = 0.048) were independently associated with moderate-to-severe WMA. PMA at sepsis diagnosis had a significant negative correlation with WM scores (r = −0.243, p = 0.039). Conclusion: PMA at sepsis diagnosis might be an important risk factor for moderate-to-severe WMA in extremely premature infants with postnatal sepsis, especially before PMA 28 weeks. Infants who suffer from sepsis before PMA 28 weeks might need additional therapy for neuroprotection.